Moral Values in the Film Chalk N Duster by Jayant Gilatar and Their Relevance for Teaching Argumentation to Students - Ammah, Erisy Syawiril; Al-Humairoh, Fuadilla Rahmah; Lestari, Sudarsri (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
The objective of this research is to analyze the moral values in the film